Convergence Measurements For Squeeze Monitoring: Instrumentation And Results - Eric R. Bauer (The National Institute for Occupational Safety and Health (NIOSH), 1981)
The magnitude and rate of advance of an inmine coal squeeze was deter-mined by measuring roof-to-floor convergence on a regular basis. A dial-gage tube extensometer was used to collect data. Using these measurements) Bureau of Mines employees drew contour maps and graphs to show the direction and rate of squeezing. Information on the rate of squeeze advance was used to determine whether steps should be taken to prevent roof and/or floor movement from closing an entire section of the mine and if alteration of mining plans was necessary to prevent further squeeze development. Data analysis revealed that the squeeze was decelerating; thus there was no need to strengthen support in the areas of the mine that were studied. Mining plans were altered, however, as a result of the findings of this investigation.